Fluxo de informação em fanfiction: uma proposta de análise sistêmico-funcional - Martins, Noara Bolzan (2015)
The theoretical perspective adopted in this study is part of a systemic-functionalist view of language. The language can be analyzed from different angles, as the postulates of Systemic Functional Grammar (SFG), which considers the texts with metafunciont encompassing ideational, interpersonal and textual meanings. The textual metafunction organizes the language in a unit of meaning (HALLIDAY; MATTHIESSEN, 2004, 2014) that allows us to recognize how we build the flow of information in texts. On the internet, a range of publications explodes daily and we realized many new textual genres arising from the heavy use of technologies and their interference in daily communication activities. Among these new genres are the fanfiction. In this sense, the objective of this study focuses on analyzing how to process the flow of textual information in fanfiction, that is, how we can build these texts as a unit of meaning. The texts are written in portuguese and published in the two largest sites of fanfiction publications in Brazil. The results show that the functional units of amusement - Theme occur mainly at the level of the clause and that the boundary between the subject and the Rheme is located immediately after the first phrasal element with a representation or representational function. The notion of theme, initially equated in terms of the clause, can provide valuable input for the analysis of textual structures. The results also show that in each phase of the text, there may be different sets of semantic topics and N-Rheme, which is essential stages of progression in the textual and therefore all the texts. We consider Theme and N-Rheme as important elements for the analysis above surfaces of sentence - in particular the thematic and rhemetic progression and development, and in general, the construction of textual structure.